1989
DOI: 10.1136/gut.30.5.634
|View full text |Cite
|
Sign up to set email alerts
|

Increased segmental activity and intraluminal pressures in the sigmoid colon of patients with the irritable bowel syndrome.

Abstract: SUMMARY Intraluminal pressure activity has been recorded in the unprepared true sigmoid colon of seven normal controls (mean age 37 years, range 22-55, three men) and seven patients with irritable bowel syndrome (IBS) (45 years, 24-75, four men) for 30 minutes before and 100 minutes after a standard 1000 kcal meal. Results differ from previously published data'3' by showing much higher indices of pressure activity with amplitudes up to 490 mmHg in IBS, and 450 mmHg in controls. Study segment activity index and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(40 citation statements)
references
References 33 publications
0
38
0
2
Order By: Relevance
“…It has been shown that IBS patients demonstrate a prolonged and exaggerated gastrocolonic response compared to control subjects [27]. The fat component of the food is the main stimulus for this response [28].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that IBS patients demonstrate a prolonged and exaggerated gastrocolonic response compared to control subjects [27]. The fat component of the food is the main stimulus for this response [28].…”
Section: Discussionmentioning
confidence: 99%
“…Richter & Bradley 109 Gastroesophageal reflux disease Sternberg et al 110 Chronic functional abdominal pain Rogers et al 111 Kellow & Phillips 112 Whitehead et al 113 Drossman et al 114 Crohn's disease Carney et al 115 Coronary artery disease Carney et al 116 It would appear that allopathic medicine is slowly adapting to the biopsychosocial model and that a whole new area of research referred to as neuropsychoimmunology has developed to investigate the model. 129 To illustrate this adaptation, Katon et al 130 found that patients with chest pain and normal coronary arteriograms had a higher level of anxiety, depression, and panic disorder than those with normal psychosocial characteristics and arteriographic studies that showed coronary stenosis.…”
Section: Does Medicine Consider the Yellow Flags In Type O Conditions?mentioning
confidence: 97%
“…In addition to the potential supraspinal influence on type M disorders, research has also shown that many type O disorders have a distinct supraspinal component (Table 6). [108][109][110][111][112][113][114][115][116][117][118][119][120][121] Furthermore, there is evidence that a reduction of this supraspinal effect may be beneficial to the patient outcome. 102,122,123 TREATMENT OF THE TYPE O CONDITION Despite anecdotal claims of success with type O conditions, success in management is not guaranteed nor is it predictable.…”
Section: Yellow Flags As the Supraspinal Influences In Chronic Pain?mentioning
confidence: 99%
See 1 more Smart Citation
“…• As stress has clearly been defined as a factor in the exacerbations of IBS, introduction of stress-reduction techniques or enrollment in formal stress-management programs can be advocated. • Fats produce an exaggerated motor responses in the small intestine and colon of patients with IBS, which may underlie the prolonged gastrocolonic responses observed in some patients [62]. The avoidance of fat is commonly recommended to prevent this enhanced contractile responsiveness.…”
Section: Treatment Of Irritable Bowel Syndromementioning
confidence: 98%